2000
DOI: 10.1016/s0010-938x(99)00071-2
|View full text |Cite
|
Sign up to set email alerts
|

Manganese dioxide as a potential cathodic reactant in corrosion of stainless steels

Abstract: Bio®lms of Leptothrix discophora SP-6, grown on 316L stainless steel (SS), ennobled the open circuit potential to 410 mV SCE. X-ray Photoelectron Spectroscopy (XPS) identi®ed MnO 2 within these bio®lms. Field exposed SS showed similar ennoblement after 30 days. XPS analysis of these samples revealed a mixture of dierent manganese minerals. Electrochemical reduction of MnO 2 was studied using electroplated SS. Plated MnO 2 was reduced amperometrically. The process was interrupted at dierent reduction stages. XP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 28 publications
5
57
0
Order By: Relevance
“…Other than this, Tafel polarization technique can also be used to study the dynamics changes of anodic and cathodic reaction caused by microorganisms or biofilm. Some studies showed that the biofilm formed in seawater can increase the depolarization in the cathodic curve 15,16].…”
Section: Polarization Curves Methodsmentioning
confidence: 99%
“…Other than this, Tafel polarization technique can also be used to study the dynamics changes of anodic and cathodic reaction caused by microorganisms or biofilm. Some studies showed that the biofilm formed in seawater can increase the depolarization in the cathodic curve 15,16].…”
Section: Polarization Curves Methodsmentioning
confidence: 99%
“…The MnO 2 can also be reduced to Mn 2 þ by accepting two electrons from metal dissolution. The intermediate product is MnOOH [52].…”
Section: C2 Microorganisms Involvedmentioning
confidence: 99%
“…Results by Linhardt [20,21] and Lewandowski et al [8,22] present a special case of ennoblement observed for SS in river waters involving formation of MnO 2 . Linhardt [20,21] found large amounts of manganese minerals (mainly MnOOH and MnO 2 ) on severely pitted SS turbine runner blades in a hydroelectric plant and suggested that pitting was due to ennoblement caused by biomineralized Mn oxides.…”
Section: Introductionmentioning
confidence: 97%
“…Johnsen and Bardal suggested that ennoblement was due to a change of the cathodic properties of the stainless steels as a result of microbial activity on the surface [7]. While it has been accepted that microbial colonization is responsible for ennoblement, a number of different explanations have been offered [8] that include microbial production of extracellular substances [9], organometallic complexes [7] or specific enzymes [10].…”
Section: Introductionmentioning
confidence: 99%